2014
DOI: 10.1007/s10826-014-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Parenting Styles and Their Associations with Mental Health and Life Satisfaction Among Urban Indonesian Adolescents

Abstract: The study aimed at investigating the association between maternal and paternal parenting styles and psychological well-being among Indonesian adolescents. The Parental Authority Questionnaire (PAQ), General Health Questionnaire-12 (GHQ-12), and the Brief Multidimensional Students' Life Satisfaction Scale, were administered to 500 adolescents. We were unable to replicate the three-factor solution of the PAQ using confirmatory factor analysis. The permissive subscale demonstrated poor psychometric properties; it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 61 publications
4
27
0
9
Order By: Relevance
“…Our study points to the importance of parenting processes for young children’s subjective well-being, adding strength to limited evidence from studies of adolescent life satisfaction [ 16 , 60 , 61 ]. It also indicates the role of parenting in mediating more distal (earlier) influences on the child.…”
Section: Discussionmentioning
confidence: 54%
“…Our study points to the importance of parenting processes for young children’s subjective well-being, adding strength to limited evidence from studies of adolescent life satisfaction [ 16 , 60 , 61 ]. It also indicates the role of parenting in mediating more distal (earlier) influences on the child.…”
Section: Discussionmentioning
confidence: 54%
“…Therefore, each participant will have score for authoritative, authoritarian, and permissive parenting for each of their father and their mother. Abubakar, Van de Vijver, Suryani, Handayani, & Pandia, (2015) showed that PAQ has high enough internal consistency reliability with Cronbach's Alpha for all the subscales was .70. In this study, based on the results of CFA and Crit, 41 items are valid to measure parenting style.…”
Section: Instrumentmentioning
confidence: 97%
“…Abundant studies have supported this contention by showing that authoritative parenting is negatively associated with adolescent mental health problems [6,11]. For example, in a study of 500 Indonesian adolescents, Abubakar et al found that both maternal and paternal authoritativeness were positively related to adolescent psychological wellbeing [38].…”
Section: The Mediating Role Of Mental Health Problemsmentioning
confidence: 99%